The revision of the genus Pterisanthes (Vitaceae) in Sumatra - Trias-Blasi, Anna; Damit, Alviana; Lucas Wambrauw, Hengky; Ahmad, Roland Putra Pribadi; Warseno, Tri; Husin, Zati (Reinwardtia, 2025)
TRIAS-BLASI, A., DAMIT, A., WAMBRAUW, H. L., AHMAD, R. P. P., WARSENO, T. & HUSSIN, Z. 2025. The revision of the genus Pterisanthes (Vitaceae) in Sumatra. Reinwardtia 24(2): 161‒184. — The genus Pterisanthes consists of 16 accepted species, with nine species being native to Sumatra, two of which are endemic to the island. Here we provide synonymy, typifications, an identification key, descriptions, distribution maps, type images, and con-servation assessments.